Langerhans cell sarcoma – a rare tumour diagnosed by histomorphology and immunophenotyping - Maraei Awadh BM,; Elnasri MA,; Tan SP,; Noraidah M, (Penerbit UKM, 2009)
Langerhans cell sarcoma is a rare neoplastic proliferation of Langerhans cells that has overt malignant cytologic features. It behaves more aggressively than its counterpart, Langerhans cell histiocytosis. We present here a case of Langerhans cell sarcoma involving the eighth thoracic vertebra in a 31-yr-old man who presented with a two-month history of back pain. In the past, the diagnosis of Langerhans cell sarcoma relied on the demonstration of Birbeck granules. However, with the advent of monoclonal antibodies suitable on routinely-fixed tissues, the Langerhans cell phenotype can be easily confirmed by CD1a protein expression using immunohistochemistry. In this report, we describe the morphological features and the immunohistochemical findings of this tumour diagnosed even in the absence of Birbeck granules. We also highlighted how immunophenotyping is useful in differentiating Langerhans cell sarcoma from other histiocytic and dendritic tumours.